Taming the Bear while Riding the Dragon? Central Asia confronts Russian and Chinese economic influences - Julien Vercueil (Revue de la Régulation)
Three waves of external influence developed in Central Asia since 1992: western, Russian and more recently, Chinese. This article aims at determine whether the Russian and the Chinese economic influences can be considered from now on as competing. It begins by distinguishing between degrees of exogeneous economic influence in order to apply this framework to the region. It then differentiates the structure of accumulation regimes among these countries and the ways they can be influenced by exogeneous changes. Third, it provides an assessment of the channels by which Chinese and Russian influence can be felt in Central Asia. Finally, it documents the current transformations that are increasing the Chinese presence and raising the risk of structural external dependency for central Asian countries.